A new approach for measuring human resource accounting - Esmat Bavali; Iman Jokar (Management Science Letters)
Significance of identifying human resource competency in organizations and the necessity for valuating human resource in accounting persuade many researchers to design a conceptual model for measuring human resource accounting. This study, first, examines dimensions of various valuation models of human resource and then they are compared with Goleman individual and social competency indicators. Next, individual, organizational and social competency indicators are designed through developing Goleman model. Finally, Analytical Hierarchy Process (AHP) and experts’ ideas in human resource accounting in superior universities of the world are used to classify the indicators; and the conceptual model of measuring human resource accounting is designed based on guidelines of management and human capital development vice-presidency and inspiring effort rate of return method.